Characterization of laboratory and real driving emissions of individual Euro 6 light-duty vehicles – Fresh particles and secondary aerosol formation. (December 2019) - Simonen, Pauli; Kalliokoski, Joni; Karjalainen, Panu; Rönkkö, Topi; Timonen, Hilkka; Saarikoski, Sanna; Aurela, Minna; Bloss, Matthew; Triantafyllopoulos, Georgios; Kontses, Anastasios; Amanatidis, Stavros; Dimaratos, Athanasios; et al.
Abstract: Emissions from passenger cars are one of major sources that deteriorate urban air quality. This study presents characterization of real-drive emissions from three Euro 6 emission level passenger cars (two gasoline and one diesel) in terms of fresh particles and secondary aerosol formation. The gasoline vehicles were also characterized by chassis dynamometer studies. In the real-drive study, the particle number emissions during regular driving were 1.1–12.7 times greater than observed in the laboratory tests (4.8 times greater on average), which may be caused by more effective nucleation process when diluted by real polluted and humid ambient air. However, the emission factors measured in laboratory were still much higher than the regulatory value of 6 × 10 11 particles km −1 . The higher emission factors measured here result probably from the fact that the regulatory limit considers only non-volatile particles larger than 23 nm, whereas here, all particles (also volatile) larger than 3 nm were measured. Secondary aerosol formation potential was the highest after a vehicle cold start when most of the secondary mass was organics. After the cold start, the relative contributions of ammonium, sulfate and nitrate increased. Using a novel approach to study secondary aerosol formation under real-drive conditions with the chase method resulted mostly in emission factors below detection limit, which was not in disagreement with the laboratory findings. Graphical abstract: Image 1 Highlights: Sub-23 nm particle emissions higher under real-drive conditions than in laboratory. Particle emissions from DPF-equipped diesel negligible under real-drive conditions. Small difference in secondary aerosol formation between laboratory and real-drive. Non-regulated ammonia emissions are a significant source of secondary aerosol. Abstract : The real-drive particle number emissions of Euro 6 gasoline vehicles exceeded those measured in the laboratory, while for a DPF equipped diesel vehicle, these emissions were mostly below the detection limit.